Advances in Breast Cancer Radiotherapy: Implications for Current and Future Practice. Issue 12 (December 2021) - Shah, Chirag; Al-Hilli, Zahraa; Vicini, Frank
Abstract : Radiation therapy (RT) is an essential component in the management of breast cancer. Following breast-conserving surgery (BCS), adjuvant RT is the standard of care for most patients. Traditionally, RT was delivered with standard whole breast irradiation (WBI) over 5-7 weeks following BCS. However, WBI regimens have evolved; hypofractionated WBI now represents the standard approach, reducing the duration of treatment to 3-4 weeks. Over the past year, five-fraction WBI regimens have also emerged as standard of care for some patients based on data from the FAST and FAST-Forward trials. An alternative to WBI that is also available for patients with early-stage breast cancer following BCS is partial breast irradiation, which can reduce the duration of treatment and the volume of breast tissue irradiated. Outcomes from multiple randomized trials with over a 10-year follow-up have demonstrated the safety and efficacy of partial breast irradiation approaches. Single-fraction intraoperative RT has also been evaluated in two prospective trials although the outcomes available, as well as current guidelines, do not support its utilization outside of prospective studies. For patients requiring RT to the regional lymph nodes, data have demonstrated the safety of hypofractionated approaches for those undergoing BCS or mastectomy without reconstruction. Future directions for early-stage breast cancer radiotherapy include the study of even shorter regimens and studies evaluating the omission of RT versus omission of endocrine therapy for favorable-risk patients. Furthermore, studies are also underway evaluating shorter courses of radiation in patients undergoing breast reconstruction and the use of tumor genomics to identify appropriate patients for omission of radiation with limited nodal involvement.